Regional Command Empowerment Strategy in Managing Natural Disasters to Assist Regional Governments in the Region (Case Study of Disasters in Makassar City) - Yepese, Edison Hadi; Gunawan, Tomy Hakim; Solikhin, Solikhin; Hidayat, Taufik; Harahap, Enda Mora (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Natural disasters have long been seen as force majore, that is, something that is beyond human control, occurring unexpectedly at what time, how it impacts and where it occurs. Natural disasters that occur will of course have an impact on large material losses, disrupt economic activities, damage infrastructure and the environment and threaten the safety of human lives and result in loss of life and property. Development programs are threatened and stopped due to the impact of natural disasters that hit areas. in Indonesia. Republic of Indonesia Law No. 34 of 2004 concerning the Main Duties of the TNI, namely Military Operations Other Than War (OMSP), including assisting in dealing with natural disasters at the emergency response, rehabilitation and reconstruction stages. Therefore, the role of the TNI AD, especially the Regional Command, in managing natural disasters is very important. Thus, this research aims to analyze the strategies implemented by the Military District Command (Kodim) 1408 in assisting the Makassar regional government in dealing with natural disasters. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and document analysis. The research results show that Kodim 1408 plays a vital role in disaster management through effective coordination, preparedness and utilization of military resources. This study provides recommendations for increasing collaboration between Kodim and local governments and increasing disaster response capacity.